Relationship between hospital length of stay and quality of care in patients with congestive heart failure. Issue 3 (1st September 2002) - Kossovsky, M P; Sarasin, F P; Chopard, P; Louis-Simonet, M; Sigaud, P; Perneger, T V; Gaspoz, J-M
Abstract : Objective: To determine the relationship between hospital length of stay (LOS) and quality of care in patients admitted for congestive heart failure (CHF). Methods: This observational study was conducted in the medical wards of the Geneva University Hospitals, Geneva, Switzerland. A random sample of 371 patients was drawn from the 1084 patients discharged alive with a principal diagnosis of CHF between January 1997 and December 1998. Explicit criteria grouped into three scores were used to assess the quality of processes of care: admission work-up (admission score); evaluation and treatment during the stay (treatment score); and readiness for discharge (discharge score). The association between LOS and quality of care was analysed using linear regression with adjustment for clinical characteristics. Results: The mean proportion of criteria met were 80% for the admission score, 66% for the treatment score, and 76% for the discharge score. Mean (SD) LOS was 13.2 (8.8) days. The admission score was not associated with LOS, but the treatment score increased by 0.5% (95% CI 0.3 to 0.7; p<0.001) with each additional day in hospital and the discharge score increased by 2.5% (95% CI 1.6 to 3.3; p<0.001) per day from admission to day 10 but remained unchanged thereafter. Adjustment for potential confounders did not substantially modify these relationships. Conclusions: In patients with CHF there is a significant association between LOS and the quality of the treatment provided, as well as with readiness for discharge. Appropriate reorganisation of processes of care should accompany attempts at reducing LOS to avoid detrimental effects on quality of care.